PROCESS AND SYSTEMS The impact of organisational change on transfusion practices in perioperative care: an analysis of blood product use following the merger of three London cardiac surgery units to form the Barts Heart Centre. Issue 1 (2020) - Anwar, Sibtain; Green, Laura; Cooper, Jackie; Curtis, Miles; Roberts, Neil; Sanders, Julie; Scully, Marie; Stables, Victoria; O'Brien, Ben
No abstract available